ACTIVE LEARNING AND GRADE 10 ACHIEVEMENT: A QUASI-EXPERIMENTAL POSTTEST COMPARISON - Razlani; Shelly Samual; Cherys Fomy Laloan (CV. TOTUS TUUS, 2026)
Teacher-centred instruction can restrict opportunities for secondary students to explain, apply, and collaboratively refine knowledge. This study compared immediate cognitive posttest achievement between two intact Grade 10 classes at SMA Negeri 1 Tompaso, Indonesia: one class received a broadly defined active-learning condition and one received conventional instruction. A quantitative non-equivalent control-group design involved 60 students, with 30 students in each class. The source record states that pretests were administered and that the achievement test underwent item-validity and internal-consistency checks; however, baseline statistics, psychometric coefficients, the academic subject, intervention duration, teacher allocation, and implementation-fidelity evidence were unavailable. Posttest scores were analysed using descriptive statistics and a two-tailed independent-samples t test after reported normality and homogeneity checks. The active-learning class obtained a higher mean (M = 83.56, SD = 3.69) than the conventional class (M = 72.40, SD = 4.49), t(58) = 9.906, p < .001, mean difference = 11.16, 95% CI [8.90, 13.41], Hedges’ g = 2.68. The result documents a large site-specific posttest association but cannot separate instructional condition from baseline class differences or other class-level influences. The study therefore offers promising contextual evidence rather than a population-wide causal estimate. Future research should use multiple classes per condition, baseline-adjusted analyses, replicable intervention protocols, validated measures, fidelity checks, and delayed assessments of retention and transfer.